ANALISIS PROSEDUR INPUT DATA DAN PEMINDAHAN BERKAS ARSIP JAMINAN KEPESERTAAN: STUDI KASUS BPJS KETENAGAKERJAAN CABANG JUANDA - Gymnastiar, Bintang; Nurhadi, Nurhadi (Jurnal Bisnis Indonesia, 2024)
In the modern era, data management has become a crucial element inorganizational operations, including BPJS Employment in Indonesia. The main focus ofthis journal is to improve the efficiency and accuracy of data input procedures andscanning of participant guarantee archive files, so that it is hoped that it can contributeto the development of these procedures. In this journal, a theoretical study regarding datainput procedures and transferring BPJS Employment archive files is explained. Theresearch method uses direct observation, allowing researchers to understand theoperational dynamics of BPJS Employment. The results and discussion include researchtasks in the general division including data input, file scanning, and file searching. Theconclusion highlights the importance of data classification, accuracy of data input, andfile retention. Suggestions involve system development and staff training at BPJSEmployment Juanda Branch.Keywords: Data Input, Archive Transfer, BPJS